Prevalence and determinants of gestational diabetes mellitus among pregnant women in India: an analysis of National Family Health Survey Data - Aditi Chakraborty; Suryakant Yadav (BMC, 2024)
Abstract Background Gestational diabetes mellitus (GDM) is a type of diabetes with its first recognition during pregnancy. GDM is a high-risk maternal and neonatal condition which increases the risk of Type 2 diabetes in mothers and their infants. It is essential to detect and treat GDM since its inception when mothers suffer from Type 1 diabetes while carrying the foetus during the gestational period. Methods The study analysed individual data from the National Family Health Survey (NFHS) surveyed in 2015-2016 (4th round) and 2019-2021 (5th round) covering a total of approximately 6 lakhs and 7 lakhs women, respectively. Among them, 32,072 women in 2015-2016 and 28,187 in 2019-2021 were pregnant, of whom 180 women in 2014-2015 and 247 women in 2019-2021 had diabetes during their gestational periods, allowing the percentage prevalence calculation of GDM. The analysis of Poisson regression estimates examined the socioeconomic and demographic risk factors for GDM among pregnant women. Results The overall prevalence of GDM in women showed an increase from 0.53% in 2015-16 to 0.80% in 2019-20 at the national level, and a similar increase in many states of India was witnessed, with a few exceptions. The GDM prevalence has shown a gradient over age, with a low prevalence in 15-19- and 25-29-year-olds and the highest prevalence in 40-44-year-olds. Concerning the rural and urban divide, its prevalence in both urban and rural areas has increased from 0.61 to 0.85% and 0.51 to 0.78% between 2015 and 16 and 2019-21. The results of the Poisson regression analysis reveal that older adults with high Body Mass Index (BMI), thyroid disorder, and heart disease have a greater risk of GDM among pregnant women in India. The states of Kerala, Meghalaya, and Goa show a high prevalence of GDM. Conclusion The low prevalence of GDM may not be clinically significant but has negative repercussions on the mother and her child cannot be overlooked. Thus, it is essential to curb GDM since its inception and save a generation ahead from the risk of diabetes and other diseases.